Trabeculectomy in Patients With Glaucoma Over 80 Years of Age: Relatively Short-term Outcomes. Issue 3 (March 2016) - Duman, Fulya; Waisbourd, Michael; Faria, Bruno; Addis, Victoria; Hsieh, Michael; Ekici, Feyzahan; Hark, Lisa A.; Spaeth, George L.
Abstract : Purpose: To compare the surgical outcomes of trabeculectomy performed in elderly patients (above 80 y) with those of younger controls. Materials and Methods: We retrospectively reviewed the charts of patients who underwent trabeculectomy from January 1, 2009 through April 30, 2011 at the Wills Eye Hospital. Patients over 80 years of age were compared with younger controls. Outcome measures included intraocular pressure (IOP), visual acuity, number of glaucoma medications, surgical complications, and surgical failure. Surgical failure was defined as when IOP>21 mm Hg or <20% reduction below baseline or IOP<5 mm Hg or reoperation for glaucoma, or loss of light perception. Results: Eighty-six eyes of patients over 80 years of age (range, 81 to 94 y) were compared with 86 eyes of younger controls (range, 22 to 79 y). Mean follow-up time was 23.9±8.0 and 25.1±8.0 months for each group, respectively. After 1 year, the failure rate was 31.3% in the elderly group, compared with 29.5% in the control group ( P =0.98). At last follow-up visit, the rate of failure between the groups was similar ( P =0.35). Postoperative complications were similar between the groups ( P =0.25). Conclusions: The surgical outcomes of trabeculectomy in patients older than 80 years were found to be similar to those of younger controls. Taking into consideration elderly glaucoma patients' general health condition and life expectancy, age alone may not be a barrier to performing glaucoma filtration surgery.